Pemahaman dan Implementasi Pencatatan Keuangan Digital pada KWT Berbasis Google Form dan Spreadsheet - Yudi Siyamto; Eka Yulianta; Yuliantoharinugroho Yuliantoharinugroho; Cinthia Mutiara Hapsari; Wilis Fahlefi (Lembaga Teewan Journal Solutions, 2026)
This community service activity aims to enhance financial literacy and digital readiness among micro, small, and medium enterprise (MSME) actors in the Women Farmer Group (KWT) Amanah, Bantul, Yogyakarta. The program focused on introducing a simple digital financial recording system using Google Form and Google Spreadsheet. The method employed was a Participatory Action Research (PAR) approach, involving 32 participants consisting of KWT members and village representatives. The implementation included three stages: preparation, execution through interactive counseling and hands-on training, and evaluation using pre-test and post-test instruments. The evaluation was based on several constructs, including financial recording behavior, digital readiness, perceived usefulness, financial self-efficacy, and user satisfaction. The results indicate that participants had a basic understanding of financial recording prior to the program but lacked consistency in practice. After the intervention, there was a significant improvement in financial self-efficacy, with an average score of 4.00, indicating increased confidence in managing financial records. However, perceived usefulness related to ease of use remained relatively low (2.00–3.00), suggesting that participants were still in the early stage of technology adoption. Overall, the program was moderately to highly successful in improving participants’ understanding and readiness toward digital financial management. The findings highlight the importance of continuous assistance to strengthen technical skills and ensure sustainable implementation of digital systems in community-based enterprises.